Transanal proctocolectomy and ileal pouch-anal anastomosis (TaIPAA) for ulcerative colitis: medium term functional outcomes in a single centre - Capolupo, G. T. (BMC Surg, 2021)
BACKGROUND: Transanal dissection of the rectum has been recently introduced for ileal pouch-anal anastomosis (IPAA) in UC showing promising results. Thanks to the precise identification of the rectotomy site the risk of long rectal stump is avoided, and a single stapled anastomosis is performed easily. The aim of this study is to analyze our initial experience of transanal proctocolectomy and ileal pouch-anal anastomosis (TaIPAA), considering postoperative complications and medium-term functional outcomes. METHODS: Our Center has experienced the transanal approach for proctectomy and IPAA since August 2018. All patients underwent Enhanced Recovery After Surgery (ERAS) protocol. Postoperative complications occurring within 30 days after surgery were taken into consideration. Fecal continence, genito-urinary activity and global quality of life at 1 and 6 months after ileostomy reversal have been assessed. RESULTS: Until March 2019, 8 patients underwent transanal proctocolectomy and ileal pouch-anal anastomosis (TaIPAA). In all cases the laparoscopic approach was performed during the transabdominal phase; abdominal drainage was never used. At the time of the pouch construction a defunctioning loop ileostomy was created in all patients. Stoma closure was performed in all cases at a median time of 6 months after surgery. Postoperative complications occurred in only one patient, who showed rectal bleeding, not required a re-invertation. There were no cases of anastomotic leakage. Medium-term functional outcomes were determined prospectively using previously validated quality of life questionnaires (Cleveland Global Quality of Life). Fecal incontinence for liquid or solid stool, genitourinary and sexual functions were also investigated, showing comparable results with the literature data. CONCLUSIONS: In our experience, transanal proctocolectomy and ileal pouch-anal anastomosis provided good short and medium-term functional results in UC.